Supramolecular Caffeic Acid and Bortezomib Nanomedicine: Prodrug Inducing Reactive Oxygen Species and Inhibiting Cancer Cell Survival - Ludwig Erik Aguilar; Se Rim Jang; Chan Hee Park; Kang Min Lee (MDPI AG, 2020)
Phenolics from plant materials have garnered attention in nanomedicine research, due to their various medicinal properties. Caffeic acid, a phenolic compound that is abundant in coffee beans, has been proven to have anticancer effects, due to its reactive oxygen species (ROS)-inducing properties. Here, a supramolecular nanomedicine was designed using caffeic acid molecule and the synthetic anticancer drug bortezomib, via catechol-boronic acid conjugation and Fe(III) ion crosslinking. Bortezomib is a proteasome-inhibiting drug and its boronic acid functional group can bind to caffeic acid's catechol moiety. By having a nanoparticle formulation that can deliver bortezomib via intracellular endocytosis, the catechol-boronic acid conjugation can be dissociated, which liberates the boronic acid functional group to bind to the 26S proteasome of the cell. The ROS-inducing property of caffeic acid also complements the bortezomib payload, as the latter suppresses the survival mechanism of the cell through NF-κB inhibition.